2016
DOI: 10.1097/mop.0000000000000328
|View full text |Cite
|
Sign up to set email alerts
|

Multielemental bioimaging of tissues in children's environmental health research

Abstract: Purpose of review Metals play major roles in children's health and are associated with negative health outcomes via deficiency, overload or toxicity. Constantly evolving analytical technology can provide new insight into how metal metabolism and exposure biology are intertwined in a range of biological matrices. Recent findings Exposure can occur prenatally as many metals cross the placental barrier. The placenta is permeable to many metal species, some through tightly regulated transporters, and others beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…291 The analysis of heavy metals in deciduous teeth is useful to reconstruct the lifetime lead exposure in children. 292,293 Arora and Austin et al 293,294 used the neonatal line as a reference line to analyze the deposition of elements (Mn, Pb) during fetal development. Savabieasfahani et al 295 found increased levels of Pb in deciduous teeth of children in war zones.…”
Section: Exposure Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…291 The analysis of heavy metals in deciduous teeth is useful to reconstruct the lifetime lead exposure in children. 292,293 Arora and Austin et al 293,294 used the neonatal line as a reference line to analyze the deposition of elements (Mn, Pb) during fetal development. Savabieasfahani et al 295 found increased levels of Pb in deciduous teeth of children in war zones.…”
Section: Exposure Sciencementioning
confidence: 99%
“…Evans et al first employed LA-ICP-MS in 1995 to measure the distribution of Zn, Sr, Cu, and Pb in teeth of walruses at different ages, and correlation of growth lines enabled the dating of past exposure events . The analysis of heavy metals in deciduous teeth is useful to reconstruct the lifetime lead exposure in children. , Arora and Austin et al. , used the neonatal line as a reference line to analyze the deposition of elements (Mn, Pb) during fetal development. Savabieasfahani et al found increased levels of Pb in deciduous teeth of children in war zones.…”
Section: Applicationsmentioning
confidence: 99%
“…Quantification of the placental metabolic capacity, in addition to structure and vascular function, can lead to a better understanding of the interaction between placental function and fetal development. For example, Austin et al 28 elaborated on the importance of evaluating the spatial distribution of elemental metal species and their role in metabolic processes, such as oxygen transportation and mitochondrial function. Deficiencies in these essential metals and/or long-term exposure to exogenous heavy metals are associated with the negative health of a child.…”
Section: Metabolismmentioning
confidence: 99%
“…The known formation timing of the different dental tissue layers offers a record of exposure to environmental pollutants including heavy metals and other trace elements deposited during mineralization (4). Laser ablationinductively coupled plasma-mass spectrometry (LA-ICP-MS) is a well-established technique used to map elements in teeth, as well as other biological tissues, at a micrometer spatial resolution (28)(29)(30). Thus, the distribution of trace elements along histologic layers in teeth has been applied mainly to rodent, human, primate, and most recently equine teeth (16,(31)(32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%